Комплекс пам’яток «Феофанія» (за матеріалами досліджень 2016—2017 рр.) - Зоценко, І.В. (Археологія і давня історія України, 2020)
У статті подані попередні результати науково-рятівних досліджень Архітектурно-археологічної експедиції, на півдні Києва. У загальних рисах розглядається структура, характер забудови та матеріальна культура давньоруського поселення Феофанія 2. The material and archaeological context of the research of Architectural and Archaeological Expedition of the IA NAS of Ukraine in 2016—2017 are considered in the paper. The group of sites dating to the 11th—13th centuries is located in the southern part of Kyiv named Feofania. This archaeological complex includes the hill-fort and three settlements.